A utilização de phyton para a resolução de problemas aplicados à Engenharia Química: implementação no ensino de cinética de processos fermentativos - Carvalho, Pâmela Oliveira de (2025)
The use of computational tools in teaching Chemical Engineering has proven to be increasingly relevant for understanding complex phenomena, in addition to being essential for process optimization and innovation in the field. Therefore, it is essential that Chemical Engineering courses offer a curriculum aligned with technological transformations and innovations, in order to prepare students for this new scenario. The objective of this work is to analyze how Python can be applied in the Chemical Engineering course at the Federal University of Ceará (UFC), focusing on the implementation of a practical class for teaching fermentation process kinetics in the Biochemical Processes and Reactors discipline. The analysis began with a brief discussion on Python applications in fundamental course concepts, such as mathematical methods, enzymatic kinetics, and chemical thermodynamics. The study then focused on the kinetics of fermentation processes, with the development and implementation of a practical class that allowed students to change variables and observe their effects on the system. The methodology involved conducting a bibliographical research on the use of the language in Chemical Engineering, followed by the application of the class and the collection of students' perceptions through a questionnaire. The results indicated that 70.6% of the students reported a significant improvement in their understanding of Monod kinetics concepts, and 82.4% strongly agreed that the Python approach could be useful in other disciplines. The experience demonstrated the potential of the language as a teaching tool, highlighting the need for a more structured integration of programming throughout the undergraduate course.